Calling the Soul Back : Embodied Spirituality in Chicanx Narrative - Garcia Lopez, Christina (Book collections on Project MUSE., 2019)
"This book shows how the Chicanx literary canon maps vital connections between mind, body, spirit, and soul"--Provided by publisher